2020
DOI: 10.3126/jom.v3i1.30912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Liquidity on Profitability in Nepalese Commercial Banks

Abstract: The aim of this paper is to examine the impact of liquidity on profitability in Nepalese commercial banks. Market price, earning per share, net profit margin and return on assets are taken as the indicators of profitability. Deposit-credit ratio, cash reserve ratio and capital adequacy ratio are taken as the indicators of liquidity. This study has tried to determine the association between liquidity and profitability indicators of 27 commercial banks out of 28 commercial banks in Nepal. The cross-sectional sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…It concluded that the independent variable has not significantly influenced profitability but has a strong and positive relationship between independent and dependent variables. The finding is similar to Adhikari's (2021) study, who has revealed that the liquidity variables have no significant impact on profitability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It concluded that the independent variable has not significantly influenced profitability but has a strong and positive relationship between independent and dependent variables. The finding is similar to Adhikari's (2021) study, who has revealed that the liquidity variables have no significant impact on profitability.…”
Section: Discussionsupporting
confidence: 90%
“…This research signifies that Bangladeshi bank will be best positioned if the equality between liquidity and profitability is maintained. Adhikari (2021) revealed the negative relationship between Liquidity and Profitability. The liquidity indicators positively and negatively impacted net profit margin, stock price, and earnings per share, but the impacts were statistically insignificant, and the overall model was also insignificant.…”
Section: A Peer-reviewed Journal Of Management and Economicsmentioning
confidence: 99%
“…The researcher observed from empirical review of literatures that the findings from the subject matter still remain relatively inconclusive and conflicting findings. have reported a negative significant relationship between liquidity and financial performance of deposit money banks globally (Sathyamoorthi et al, 2020;Eze & Agu, 2020), while other studies reported no significant impact of liquidity on financial performance of commercial banks (Adhikari, 2020). The inconsistent results could be a result of changes in the study's environment, time period, measurements, data analysis method, or analysis tools.…”
Section: Literature Gapmentioning
confidence: 95%
“…Additionally, to establish the effect of liquidity on profitability, Adhikari (2020) studied the effect of of liquidity on profitability in Nepalese commercial banks. 27 out of 28 commercial banks in Nepal were used for the analysis.…”
Section: Empirical Reviewmentioning
confidence: 99%